(untitled) (Acta Entomologica Serbica, 2019)
Asianellus festivus (C. L. Koch, 1834) is a new species of jumping spider for Serbian fauna. It is recorded at the localities of Bresje and Leštar in the vicinity of Jagodina. Data on biology and ecology of species, photographs of male and female habitus and drawings of copulatory organs are given.